Regional differences in biochemical markers of coronary artery disease: insights from East, West, Central and North-East India - Singh, Shashwat; Sharma, Akhil Kumar; Swaroop, Suchit (International Journal Of Community Medicine And Public Health, 2025)
Coronary artery disease (CAD) continues to be a major cause of illness and death in India, showing clear regional differences shaped by lifestyle, dietary habits, and genetics. Although dyslipidemia is a key risk factor, few studies have compared biochemical profiles across multiple regions. This review (2014-2024) analyzed data from eighteen peer-reviewed studies covering West, Central, East, and North-East India. These included hospital-based cohorts of CAD, acute coronary syndrome (ACS), and acute myocardial infarction (AMI) patients, along with some community-based studies. The biochemical parameters evaluated were total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG), fasting glucose, and HbA1c. Multivariate analysis of variance (MANOVA) assessed regional differences. A general pattern of atherogenic dyslipidemia was consistent nationwide, marked by high TC, LDL-C, and TG with low HDL-C. Central India reported extreme dyslipidemia among diabetic AMI patients, while Western India showed widespread lipid imbalance along with high hs-CRP and Lp(a) levels. Eastern India exhibited strong associations with metabolic syndrome and glycemic irregularities, particularly in urban populations. The North-East highlighted the combined influence of tobacco, alcohol, and high-salt diets on lipid and glucose profiles. MANOVA showed that TC differed significantly by region (p=0.025), while LDL-C, HDL-C, and TG patterns were relatively similar. Overall, CAD in India is characterized by low HDL-C, high LDL-C, and raised TG levels, but total cholesterol varies regionally. Targeted preventive measures and region-based lipid monitoring are essential to reduce CAD risk nationwide.